2021
DOI: 10.21203/rs.3.rs-214439/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Appendectomy During the COVID-19 Pandemic in Italy. A Multicenter Ambispective Cohort Study by the Italian Society of Endoscopic Surgery and new technologies (the CRAC study).

Abstract: Background To determine on a national basis the surgical activity regarding appendectomies during the first Italian wave of the COVID-19 pandemic. Major surgical societies advised using non-operative management of appendicitis and suggested against laparoscopy during the COVID-19 pandemic. Methods Multicenter, observational study investigating the outcomes of patients undergoing appendectomy in the two months of March-April 2019 vs. March-April 2020. The primary outcome was the number of appendectomies perfor… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
9
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(10 citation statements)
references
References 22 publications
1
9
0
Order By: Relevance
“…The lower negative appendectomy rate in the COVID period may be attributed to strict selection criteria, entailing an increased use of CT scans that were applied before appendectomy during the COVID-19 period. This was to avoid non-indicated surgery and unnecessary use of operation rooms and resources at these difficult times [31,32,53,54,59].…”
Section: Discussionmentioning
confidence: 99%
“…The lower negative appendectomy rate in the COVID period may be attributed to strict selection criteria, entailing an increased use of CT scans that were applied before appendectomy during the COVID-19 period. This was to avoid non-indicated surgery and unnecessary use of operation rooms and resources at these difficult times [31,32,53,54,59].…”
Section: Discussionmentioning
confidence: 99%
“…Changes in resources availability were also presented in most studies (REF?). Three out of the ten studies in our meta-analysis suggested significantly higher rate of postoperative complications (22) and one of the two reported more severe complications in the COVID -19 era compared to the control cohort (24). Both studies were conducted in the first COVID -19 wave in Italy which was one of the first countries to experience the SARS-COV-2 outbreak.…”
Section: Discussionmentioning
confidence: 73%
“…Massive employment of health care resources resulted in canceling and postponing surgeries. Some studies reported an increase in postoperative complications (24,55,56). As far as we aware this study is among first systematic reviews studying on complication of surgeries during the pandemic so far.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations